Herpes encephalitis : a stroke mimicker - Thein Win; Nida Maham; Sahayini Kumar (Greater Baltimore Medical Center, 2019)
Background: HSV-1 encephalitis (HSVE) usually presents with fever, altered mental status or focal seizures. Aphasia can also be a presenting symptom of HSVE but rarely occurs as the primary symptom. We present a case where aphasia was the primary presenting symptom of HSVE. Case: A 72-year-old physician with a history of hyperlipidemia and obstructive sleep apnea presented to the emergency room with sudden onset of speech difficulty lasting an hour. He did not have a fever, photophobia, neck stiffness, weakness, or numbness. The patient was brought in by the family within an hour to the emergency department. On exam, the only neurological deficit that was found was the use of inappropriate words in sentences and inability to name certain objects. He was diagnosed with an embolic stroke and received tPA. MRI brain that was done 24-hour post tPA showed an increased FLAIR and T2 signal hyperintensity within the medial left temporal lobe with slight effacement of the cysts sulci which was concerning for encephalitis. This was later confirmed by serology. The patient was started on IV Acyclovir and recovered fully after 3 weeks of acute neuro rehabilitation. Conclusion: Aphasia primarily is an unusual presentation of HSVE. It should be considered as one of the possibilities in patients presenting with features suggestive of a stroke involving the language areas of the brain.